Prespektif Al Qur'an Dalam Manajemen Waktu Penghafal Al Quran - Suci Istriana; diah Sadiah; Selvi sri wahyuni Sesep rustandia; Fahmi Suhaemia; Irfan Maulanaa, (Universitas Ibn Khaldun Bogor, 2023)
this study discusses how the perspective of the Koran in time management for memorizing the Koran using the library research method with the maudu'i interpretation approach is different from previous research discussing study time according to the Koran and also study time according to Ulama and in this study aims to focus on learning activities, namely memorizing the Koran and the results of this study are that it can be understood that effective time management according to the Koran is memorizing in the morning from before dawn and also at night to repeat the memorization and this is based on the basis of 2 verses in the Koran namely sura al muzammil verse 6 and also the letter Al furqan.62.